2007
DOI: 10.1243/09544097jrrt66
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the life of steel rails

Abstract: A model of plastic strain accumulation, wear, and rolling contact fatigue (RCF) crack initiation in rail steel has been developed. Local to the contact zone, material is subject to severe cyclic stresses taking it beyond yield and leading to incremental accumulation of plastic deformation (ratcheting). This model is based on a ratcheting law derived from twin-disc, rolling-sliding contact experiments and can simulate thousands of ratcheting cycles with corresponding strain hardening. The model is being further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Past work on rails removed from service [4, 14,15,21,22,23] has shown that vertical, angled sections normal to, and through the centre of, an RCF crack, i.e. cut in the direction of the maximum vector of composite creepage, give a clearer picture of crack severity and microstructural strain than seen with axial and transverse vertical sections, where crack branching and multi-crack interactions can confuse the analysis.…”
Section: Crack Shape Observation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past work on rails removed from service [4, 14,15,21,22,23] has shown that vertical, angled sections normal to, and through the centre of, an RCF crack, i.e. cut in the direction of the maximum vector of composite creepage, give a clearer picture of crack severity and microstructural strain than seen with axial and transverse vertical sections, where crack branching and multi-crack interactions can confuse the analysis.…”
Section: Crack Shape Observation Methodsmentioning
confidence: 99%
“…This has been modelled in 2D for various PE ferrite widths at the PA boundary by Franklin et al [14,16]. A 3D model of this very early crack formation and growth is being developed; the PA grain distribution has been represented by a volume (with periodic boundaries) of convex polyhedra (Figure 7a) with paths for potential crack growth along the representative PA grain boundaries mapped over time as the microstructure deforms plastically.…”
Section: Modelling Of Crack Initiation and Very Early Growthmentioning
confidence: 99%
“…The depth of the notches varied between 2 and 15 mm, while for more realistic representation of RCF cracking certain notches were angled with respect to the surface normal and the rail edge and the railhead surface. RCF head checks detected in rails are often inclined to the surface, penetrating initially at a shallow angle of approximately 15-301 until they reach a characteristic depth and turn down into the railhead at an angle of approximately 601 [24,25]. Fig.…”
Section: Experimental Details For the Spinning Rail Rig Testsmentioning
confidence: 99%
“…Where, H n is Nano-indentation hardness (compressive load: 30 mN), with different values applied depending on material phases. β is also a material-dependent constant (pro-eutectoid ferrite: 1.48, pearlite: 1.5 [4], and τ max : maximum value of orthogonally crossing shear stress within the cross section. γ c (critical value of γ) is taken here as 2.89 (= tan (90° -19.08°), by applying the head checking angle as 19.08° (mean value) according to [5].…”
Section: Analytical Programmentioning
confidence: 99%